2022
DOI: 10.1002/jbt.23129
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol mitigates diclofenac‐induced hepatorenal toxicity in rats via modulation of miR‐144/Nrf2/GSH axis

Abstract: Despite the extensive therapeutic uses of diclofenac, it may cause several adverse effects, including hepatorenal injury. The antioxidant and anti-inflammatory properties of resveratrol, a polyphenolic compound, make the agent effective in ameliorating a variety of drug-induced injuries. This study investigated the potential beneficial effects of resveratrol on diclofenac-induced hepatorenal toxicity and explored the role of miR-144 and its relationship to oxidative stress and inflammation triggered by diclofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Also, the histopathological findings of the current study proved the hepatic damage induced by diclofenac, which is consistent with the previous report of (Esmaeilzadeh et al, 2020). Concerning renal function, previous studies by (Izak-Shirian et al, 2022) and (Elbaz et al, 2022) reported obvious nephrotoxicity after diclofenac administration to rats at a dose (50 mg/kg) for 5 days and (10 mg/kg) for 7 days. These results were consistent with the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Also, the histopathological findings of the current study proved the hepatic damage induced by diclofenac, which is consistent with the previous report of (Esmaeilzadeh et al, 2020). Concerning renal function, previous studies by (Izak-Shirian et al, 2022) and (Elbaz et al, 2022) reported obvious nephrotoxicity after diclofenac administration to rats at a dose (50 mg/kg) for 5 days and (10 mg/kg) for 7 days. These results were consistent with the current study.…”
Section: Discussionsupporting
confidence: 92%
“…found that resveratrol also triggers the downregulation of miR-144 by upregulating the expression level of Nrf2.Consequently, resveratrol showed hepatorenal antioxidant, anti-inflammatory, and antiapoptotic activities as manifested by improvement in the antioxidant markers along with a decline in NF-κB, TNF-α, and caspase-3 expressions. In summary, this study demonstrated that resveratrol has potential therapeutic effects in alleviating liver and kidney damage induced by nonsteroidal anti-inflammatory drugs ( 275 ).…”
Section: The Challenges Faced In the Clinical Application Of Resverat...mentioning
confidence: 77%
“…Nrf2 is a nuclear transcription factor which has an essential role in the antioxidant defense process regulation. 49,50 Normally, Nrf2 is degraded in the cytoplasm. 49 Under stressed conditions, it undergoes nuclear translocation, where it binds to the antioxidant response element (ARE) to induce the transcription of many antioxidant enzymes such as glutathione S-transferase, heme oxygenase-1, catalase, and superoxide dismutase.…”
Section: Discussionmentioning
confidence: 99%